2016
DOI: 10.1111/liv.13172
|View full text |Cite
|
Sign up to set email alerts
|

Selective intestinal decontamination with norfloxacin enhances a regulatory T cell‐mediated inflammatory control mechanism in cirrhosis

Abstract: These results provide a plausible mechanism for the immunomodulatory effects of norfloxacin in cirrhosis beyond its bactericidal effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
5
12
0
Order By: Relevance
“…BT is a common accepted mechanism for the development of significant bacteria‐related complications in cirrhosis, and its prevention must be considered as a permanent goal during disease progression. In the past, we have reported that Treg cells are relevant to the inverse correlation observed between bacterial antigen translocation and norfloxacin through the anti‐inflammatory cytokine IL‐10 in CCl 4 ‐induced cirrhosis . In the present study, we show in vivo that gut permeability to bacterial antigens is sensitive to the Treg cell population in cirrhotic mice, as orally administered LPS recovered in blood is significantly increased in cirrhotic mice lacking adaptive immunity, and it is down‐regulated when these mice are cotransferred with spleen‐derived naive T and Treg cells from WT donors (Fig.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…BT is a common accepted mechanism for the development of significant bacteria‐related complications in cirrhosis, and its prevention must be considered as a permanent goal during disease progression. In the past, we have reported that Treg cells are relevant to the inverse correlation observed between bacterial antigen translocation and norfloxacin through the anti‐inflammatory cytokine IL‐10 in CCl 4 ‐induced cirrhosis . In the present study, we show in vivo that gut permeability to bacterial antigens is sensitive to the Treg cell population in cirrhotic mice, as orally administered LPS recovered in blood is significantly increased in cirrhotic mice lacking adaptive immunity, and it is down‐regulated when these mice are cotransferred with spleen‐derived naive T and Treg cells from WT donors (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Among adaptive IL‐10‐producing cells, Treg cells are especially relevant because of their homeostatic role in the host–microbe interaction. We have identified increased rates of Treg cells in patients on selective intestinal decontamination, their correlation with serum norfloxacin concentrations, and their role as relevant IL‐10–secreting cells in these patients, supporting their implication in norfloxacin‐derived down‐regulation of serum proinflammatory levels in cirrhosis observed in the past . In addition, this cell type is implicated in gut homeostatic functions, as their role in modulating SCFAs concentration in the gut microbiota has been reported …”
supporting
confidence: 74%
See 1 more Smart Citation
“…General markers of systemic inflammation such as pro‐inflammatory cytokines have been reported with increasing ACLF grades and associated increased mortality . Studies of systemic and nonabsorbable antibiotics in cirrhosis have demonstrated that such treatments can decrease inflammatory cytokines and improve hemodynamic circulation in the context of intestinal decontamination and decreased gut bacterial translocation . However, HRS is not completely preventable by antibiotics, nor can we reverse HRS associated with infection by treatment of infection alone .…”
Section: Discussionmentioning
confidence: 99%
“…(9,10) Studies of systemic and nonabsorbable antibiotics in cirrhosis have demonstrated that such treatments can decrease inflammatory cytokines and improve hemodynamic circulation in the context of intestinal decontamination and decreased gut bacterial translocation. (33)(34)(35)(36)(37)(38) However, HRS is not completely preventable by antibiotics, nor can we reverse HRS associated with infection by treatment of infection alone. (39,40) Even with regimens including supportive care and HRS-directed therapies such as terlipressin and intravenous albumin, there is an increased HRS treatment-failure rate at higher ACLF grades.…”
Section: Discussionmentioning
confidence: 99%